2015
DOI: 10.2340/16501977-2006
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and course of work-participation in patients with chronic non-specific low back pain: A 12-month follow-up cohort study

Abstract: At 12 months 52% of patients reported ≥ 90% work-participation. The strongest prognostic factor was more work-participation at baseline for the recovery of chronic non-specific low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…The mean age of the participants was 44 years, and the cohort included a slightly higher percentage of women than men. These characteristics were in accordance with other studies [4,9,38,39], indicating that the population we studied is representative of a Norwegian population with CLBP. People with CLBP are assumed to have a poor prognosis concerning return to work (RTW) [40].…”
Section: Discussionsupporting
confidence: 92%
“…The mean age of the participants was 44 years, and the cohort included a slightly higher percentage of women than men. These characteristics were in accordance with other studies [4,9,38,39], indicating that the population we studied is representative of a Norwegian population with CLBP. People with CLBP are assumed to have a poor prognosis concerning return to work (RTW) [40].…”
Section: Discussionsupporting
confidence: 92%
“…However, there was a steady increase in the number of patients who recovered their work capability during the follow-up, which confirmed the program’s long-term benefits. Although research has shown that return-to-work interventions are most successful when administered to patients whose incapability to work was shorter [37], this factor was not found to significantly affect return to work in our population.…”
Section: Discussionmentioning
confidence: 68%
“…One weakness of utilizing national databases to obtain sick leave information is that the reasons for taking sick leave are not adequately registered in these databases. 20,24 It is known that CLBP has a fluctuating course; thus, we chose to register part-time sick leave, which provided us with a more nuanced picture than that obtained by research that only distinguishes between full-time work and full-time sick leave. 17,25,26 …”
Section: Discussionmentioning
confidence: 99%
“…However, several recent studies have found that work-specific interventions are not preferable when RTW is the main outcome. 21,24,30 …”
Section: Discussionmentioning
confidence: 99%